Analisis Pengaruh Temperatur Tuang Dan Ukuran Butiran Pasir Terhadap Kekerasan Dan Struktur Mikro Hasil Cor Kuningan Pada Pengecoran Evaporative - Predi Apriadi, I Putu; Sugita, I Ketut Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstractt Casting is a process of pouring liquid metal into a mold to form a workpiece, one of which is the manufacturing process using brass material. Brass is a material composed of a mixture of Cu-Zn, where this mixture is considered stronger and harder than copper. However, it is possible to further enhance the quality of brass material with different treatments. One of the efforts that can be done is by varying the pouring temperature and the size of the sand grains used. In this study, evaporative casting was used with pouring temperature treatments of 900?, 1000?, and 1100?, and sand grain sizes of 0.250mm, 0.315mm, and 0.500mm. The results obtained from the Vickers hardness testing showed that the hardness value of the material decreased with increasing pouring temperature. The highest hardness value was obtained at a temperature of 900? with a sand grain size of 0.500mm, measuring 203.65 HVN. On the other hand, the lowest hardness value was obtained at a temperature of 1100? with a sand grain size of 0.315mm, measuring 175.49 HVN. The observation of the microstructure revealed that there were changes in the grain structure of Cu-Zn with increasing pouring temperature. Keywords: Evaporative Casting, Size Of Sand Grains, Violence, Microstructure